2022
DOI: 10.3389/fmicb.2021.806626
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Malignancy in Trypanosoma brucei brucei by Rapid Passage in Mice

Abstract: Pleomorphic Trypanosoma brucei are best known for their tightly controlled cell growth and developmental program, which ensures their transmissibility and host fitness between the mammalian host and insect vector. However, after long-term adaptation in the laboratory or by natural evolution, monomorphic parasites can be derived. The origin of these monomorphic forms is currently unclear. Here, we produced a series of monomorphic trypanosome stocks by artificially syringe-passage in mice, creating snapshots of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…To explore the initiation of this phenotypic change, we performed laboratory selection to generate monomorphism de novo. In five independently selected clonal lineages this generated consistent changes in the transcriptome, with key posttranscriptional regulators showing altered expression, including two with established roles in life cycle progression (RBP10, ZCH20); previous selections for monomorphism have also identified changes in posttranscriptional regulators 42,43 .…”
Section: Discussionmentioning
confidence: 74%
“…To explore the initiation of this phenotypic change, we performed laboratory selection to generate monomorphism de novo. In five independently selected clonal lineages this generated consistent changes in the transcriptome, with key posttranscriptional regulators showing altered expression, including two with established roles in life cycle progression (RBP10, ZCH20); previous selections for monomorphism have also identified changes in posttranscriptional regulators 42,43 .…”
Section: Discussionmentioning
confidence: 74%
“…For example, it has been demonstrated that several trypanosomal proteins such as RBP7, YAK or MEKK1, TbGPR89 and others are involved in the stumpy induction factor signaling pathway and cell differentiation in T. brucei (McDonald et al, 2018;Silvester et al, 2018;Rojas et al, 2019). Furthermore, a recent study which generated monomorphic T. brucei, from a pleomorphic strain, confirmed that changes in the transcriptome of nuclear genes were associated with this transformation (Cai et al, 2022). Unlike kinetoplast DNA, which is required for the development and adaption in the insect, nuclear genes seem to perform a more important function in the differentiation between the mammalian bloodstream stages.…”
Section: Introductionmentioning
confidence: 82%
“…Several cell surface proteins have also been proved to be responsible for the transduction of stumpy induction factor (SIF) signaling within cells (Mony and Matthews, 2015;McDonald et al, 2018;Rojas et al, 2019). Interestingly, defects in quorum sensing pathways have recently been reported in T. evansi and T. equiperdum but also in artificially selected monomorphic lines of T. brucei (Cai et al, 2022). These parasites are normally almost indistinguishable from each other, using a wide range of molecular markers (Gibson et al, 1980;Lun et al, 1992a;Lun et al, 1992b;Lai et al, 2008;Verney et al, 2020), which makes it all the more interesting that these differences map onto the quorum sensing pathways.…”
Section: Discussionmentioning
confidence: 99%